2021
DOI: 10.1093/humrep/deab126.051
|View full text |Cite
|
Sign up to set email alerts
|

O-126 Endometrial microbiota composition is associated with reproductive outcome in infertile patients

Abstract: Study question Is there an association between the composition of the endometrial microbiota and the reproductive outcomes in infertile patients undergoing in vitro fertilization (IVF)? Summary answer The composition of the endometrial microbiota (EM) prior to embryo transfer is associated with the different reproductive outcomes: live birth, no pregnancy or clinical miscarriage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…Corroborating these findings, a prospective observational multicenter study including 342 infertile patients demonstrated that higher abundance of Lactobacillus strongly correlated to LBR, suggesting that Lactobacillus could be a biomarker for treatment success [ 18 ]. However, the presence of Atopobium , Bifidobacterium , Chryseobacterium , Gardnerella , Haemophilus , Klebsiella , Neisseria , Staphylococcus , and Streptococcus was associated with worse prognosis after ART treatment (e.g., no pregnancy, biochemical pregnancy, or clinical miscarriage).…”
Section: Endometrial Microbiota Composition and Reproductive Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Corroborating these findings, a prospective observational multicenter study including 342 infertile patients demonstrated that higher abundance of Lactobacillus strongly correlated to LBR, suggesting that Lactobacillus could be a biomarker for treatment success [ 18 ]. However, the presence of Atopobium , Bifidobacterium , Chryseobacterium , Gardnerella , Haemophilus , Klebsiella , Neisseria , Staphylococcus , and Streptococcus was associated with worse prognosis after ART treatment (e.g., no pregnancy, biochemical pregnancy, or clinical miscarriage).…”
Section: Endometrial Microbiota Composition and Reproductive Outcomesmentioning
confidence: 99%
“…However, the presence of Atopobium , Bifidobacterium , Chryseobacterium , Gardnerella , Haemophilus , Klebsiella , Neisseria , Staphylococcus , and Streptococcus was associated with worse prognosis after ART treatment (e.g., no pregnancy, biochemical pregnancy, or clinical miscarriage). For instance, Gardnerella , Klebsiella , and Streptococcus were significantly increased in non-pregnant patients, Klebsisella and Staphylococcus were related to clinical miscarriage, and Enterococcus was enriched in subjects that had a biochemical pregnancy [ 18 ].…”
Section: Endometrial Microbiota Composition and Reproductive Outcomesmentioning
confidence: 99%
See 3 more Smart Citations